Development of Android-based Javanese language “Pawarta” learning media using Adobe Animate software - Yusnita, Windi; Dwijonagoro, Suwarna (Diksi, 2025)
Javanese language learning aims to preserve regional languages ​​and introduce local cultural values ​​to the younger generation, especially in the midst of globalization that is shifting the use of Javanese. Understanding the material and motivation are challenges for students in learning Javanese. This is due to the lack of learning media. Therefore, this study discusses the development of Android-based learning media "Sinau Pawarta Basa Jawa" created using Adobe Animate software. This study aims to increase students' interest in learning, improve understanding of Javanese language learning materials, and foster awareness of learning Javanese. The research method used is Research and Development with the ADDIE model. The results of the study showed that learning media was able to significantly increase students' understanding and interest in learning Javanese. The use of this application makes the learning process more interactive and interesting, so that students are more enthusiastic in learning activities. In conclusion, this learning media is not only able to improve news writing skills, but also becomes an innovative solution in preserving Javanese among the younger generation through a technology-based interactive learning approach. Further research can also integrate application technology to increase student engagement in the era of Society 5.0.